Pandangan Ulama Tentang Metode Tafsir Tahlili - Muhammad Ghoust; Halimatussa’diyah; Kusnadi (Jurnal Cakrawala Akademika, 2024)
This study discusses the tahlili tafsir method, which is used to understand the verses of the Qur’an in depth by analyzing the meanings contained within. The background of this research focuses on the importance of accurate comprehension of the Qur’an in the context of the modern era, which is becoming increasingly complex. The purpose of this research is to understand the views of scholars on the tahlili tafsir method and its contribution to interpreting sacred texts. The method used in this research is literature study, analyzing both classical and contemporary tafsir works. The findings of this research show that the tahlili tafsir method has the advantage of understanding the Qur’an holistically, covering aspects of language, history, law, and social context. The implication of this research is the importance of continuously developing and updating tafsir methods to address contemporary challenges and the needs of the Muslim community today.